Consumer Attitude towards Marketing Practices in Vietnamese Smartphone Market - Linh, Nguyen Khanh; Ha, Nguyen Thu (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2016)
Abstract This study aims to investigate customer attitudes towards marketing activities in the smartphone market inVietnam. In order to reach this aim, the index of consumer sentiment towards marketing, which is based on the marketing mix paradigm (4Ps), is adopted. The findings show a positive relationship among four components of the marketing mix (including product, price, place and promotion) and customer satisfaction, among which the “product” component has the most significant impact on customer satisfaction. Thus, the study indicates meaningful implications for marketers in the process of enhancing the customer satisfaction level in practice. Received 15 July 2015, revised 9 June 2016, accepted 28 June 2016 Keywords: Attitude, consumer sentiment towards marketing, customer satisfaction, marketing mix, smartphone, Vietnam.